2018
DOI: 10.1142/s0219455418500694
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis of an Integrated Train–Bridge–Foundation–Soil System by the Substructure Method

Abstract: The substructure method is applied to the dynamic analysis of a train–bridge system considering the soil–structure interaction. With this method, the integrated train–bridge–foundation–soil system is divided into the train–bridge subsystem and the soil–foundation subsystem. Further, the train–bridge subsystem is divided into the train and bridge components. The frequency-dependent impedance function of the soil–foundation subsystem is transformed into time domain by rational approximation and simulated by a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Gara et al [8] discussed the contribution of SSI to the bridge dynamics, and found that SSI may significantly affect the structural dynamics, especially in the case of soft or medium soil deposits. Qiao et al [9] established an analytical model of the train-bridge system considering SSI based on the substructure method, and found that it is important to consider SSI in the dynamic analysis of train-bridge systems, but such influence becomes weaker with the increase in the soil shear wave velocity. Tochaei et al [10] investigated the effects of soil-structure interaction and near-field seismic ground motions on cable-stayed bridges based on experiments and numerical analysis; their results indicated that the effect of foundation soil stiffness on the response of the bridge was influenced by the type of input ground motion and that the bridge response was amplified when their foundation was in softer soils.…”
Section: Introductionmentioning
confidence: 99%
“…Gara et al [8] discussed the contribution of SSI to the bridge dynamics, and found that SSI may significantly affect the structural dynamics, especially in the case of soft or medium soil deposits. Qiao et al [9] established an analytical model of the train-bridge system considering SSI based on the substructure method, and found that it is important to consider SSI in the dynamic analysis of train-bridge systems, but such influence becomes weaker with the increase in the soil shear wave velocity. Tochaei et al [10] investigated the effects of soil-structure interaction and near-field seismic ground motions on cable-stayed bridges based on experiments and numerical analysis; their results indicated that the effect of foundation soil stiffness on the response of the bridge was influenced by the type of input ground motion and that the bridge response was amplified when their foundation was in softer soils.…”
Section: Introductionmentioning
confidence: 99%
“…Rocha et al [26,27] assessed the train running safety passing through bridges based on the probability density evolution method. Other studies include train-bridge coupled simulation of a composite structure bridge [28], train-bridge coupled vibration analysis considering environmental wind loads [29,30], and the interaction between the train-bridge system and the foundation-soil system by the substructure method [31].…”
Section: Introductionmentioning
confidence: 99%